The Presupposition Analysis In “Oppenheimer” Movie : Pragmatic Study - Fabian, Muhammad Rifki; Heryono, Heri (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2024)
This study purposes to analyze the pragmatic theories of Oppenheimer movie. This research aims to conduct a pragmatic analysis of presuppositions in the film "Oppenheimer." Presuppositions are implicit assumptions conveyed through language that shape the audience's understanding of the narrative. The study employs tools from pragmatics to investigate how presuppositions are employed in the movie, specifically focusing on their role in shaping character relationships, plot development, and overall discourse. The research methodology involves a close examination of the linguistic and contextual elements within the movie's dialogue and narrative structure. Finding the presuppositions of said movie, categorizes the presupposition theories. Gather all the data and reach a conclusion of the movie. The findings of this study are expected to provide insights into the pragmatic strategies employed by the filmmakers to convey information and evoke specific emotional responses from the audience. Additionally, the research contributes to the broader understanding of presupposition analysis in cinematic discourse, offering a nuanced perspective on how language is used to convey meaning beyond explicit statements. This investigation is particularly relevant in the context of Oppenheimer, a film known for its historical and intellectual depth. By exploring presuppositions in this cinematic context, the study contributes to the interdisciplinary dialogue between linguistics and film studies, shedding light on the intricate ways in which language shapes narrative comprehension in the medium of film.